Effect of Bi-B-Si-Zn-Al glass additive on the properties of low-temperature sintered silicon carbide ceramics - Zhang, Lan; Yang, Shuquan; Xiao, Meihui; Chen, Lin; Sun, Jun; Ding, Jianjun; Li, Xiaoxiao; Gong, Yi; Zheng, Kang; Zhang, Xian; Tian, Xingyou (Frontiers in Physics, 2023)
In this study, the performance of low-temperature sintered Bi-B-Si-Zn-Al glass/SiC composites by vacuum hot-press sintering between 700°C and 1000°C was investigated. The specimen had a relatively preferable density of 95.5% and thermal conductivity of 8.660 Wm−1K−1 after sintering at 900°C for 2 h. The dielectric constant and dielectric loss tangle of the composite were 32.9 and 0.57 at 20 GHz, respectively. The XRD analysis indicated the formation of Bi, Zn and ZnAl2O4 crystals, and the microstructure showed the low contact angle of the glass and SiC grain. Such low-temperature sintered SiC ceramic may have a promising application in the electronic field.